Safety of JAK and IL-6 inhibitors in patients with rheumatoid arthritis: a multicenter cohort study - Yoshida, Shuhei; Miyata, Masayuki; Suzuki, Eiji; Kanno, Takashi; Sumichika, Yuya; Saito, Kenji; Matsumoto, Haruki; Temmoku, Jumpei; Fujita, Yuya; Matsuoka, Naoki; Asano, Tomoyuki; Sato, Shuzo; et al. (Frontiers in Immunology, 2023)
Background The ORAL Surveillance trial showed a potentially higher incidence of malignancy and major adverse cardiovascular events (MACEs) associated with tofacitinib than those associated with tumor necrosis factor (TNF) inhibitors (TNFis). However, few studies have compared the safety of non-TNFis or other Janus kinase (JAK) inhibitors (JAKis). This study was aimed at comparing the incidence rates (IRs) of malignancies and MACEs in patients with rheumatoid arthritis (RA) treated using interleukin-6 (IL-6) inhibitors (IL-6is) or JAKis. Methods We retrospectively analyzed 427 patients with RA who were treated using an IL-6i (n = 273) or a JAKi (n = 154). We determined the IRs of malignancy and MACEs, and the standardized incidence ratio (SIR) of malignancies and investigated factors related to malignancy and MACEs. After adjusting the clinical characteristic imbalance by propensity score matching (PSM), we compared the IRs of adverse events between the JAKi and IL-6i groups. Results After PSM, the observational period was determined to be 605.27 patient-years (PY), and the median observational period was determined to be 2.28 years. We identified seven cases of malignancy (IR: 2.94 per 100 PY) in the JAKi-treated group and five cases (IR: 1.36 per 100 PY) in the IL-6i-treated group after PSM. The IR of MACEs was 2.56 and 0.83 (per 100 PY) in the JAKi- and IL-6i-treated groups. The IRRs of JAKi-treated patients versus IL-6i-treated patients were 2.13 (95% confidence interval (CI): 0.67–7.42) for malignancy and 3.03 (95% CI: 0.77–15.21) for MACE. There were no significant differences in IRR for malignancy and MACE between both groups after PSM. Univariate and multivariable Cox regression analyses revealed that older age and JAKi use were independent risk factors for malignancy, while older age, hypertension, and JAKi use were independent risk factors for MACEs. The overall malignancy SIR was significantly higher in the JAKi-treated group compared to the general population (2.10/100 PY, 95% CI: 1.23–2.97). Conclusion The IRs of malignancy and MACE in patients with RA after PSM were comparable between IL-6i-treated and JAKi-treated patients. However, the SIR of malignancy in JAKi treatment was significantly higher than in the general population; therefore, further safety studies comparing JAKi to non-TNFi biologic disease-modifying antirheumatic drugs (bDMARDs) are needed.